Theological Hermeneutics and Discourse About God as Seen by Juan José Tamayo-Acosta - Gardocki, Dariusz (Verbum vitae, 2025)
One of the important tasks and at the same time challenges facing theology of all times is how to speak about God in an understandable way. This is due to the fact that God is an incomprehensible mystery that exceeds human cognitive abilities. As well as with the multiplicity of existing concepts and images of God not only in different religions, but also often within the same religion. The task of theology is to help us understand both how God reveals himself to us and what he communicates to us about himself in his word, especially in the person of Jesus Christ. The purpose of this article is to show how God can and should be spoken of in theology today according to Spanish theologian Juan José Tamayo- Acosta. The first point presents theological hermeneutics as an essential tool in rethinking in a new way God’s self-revelation in history, as well as in understanding dogmas. The second point discusses the need to include language in discourse about God, which refers to symbols and metaphors as means that express meaning better than concepts alone the mystery of God. In the third point, Christian mysticism is shown as an example of a metaphorical way of talking about God.